Association Between Sitting Duration, Learning Posture, and Musculoskeletal Complaints Among High School Students - Muchamad Ardi Putrawardana; Ketut Holifah (Lembaga Kajian Ilmu Pengetahuan dan Publikasi Indonesia, 2025)
Prolonged sitting duration and non-ergonomic learning postures are major risk factors for musculoskeletal disorders among adolescents. High school students spend most of their time sitting during academic activities, gadget use, or independent study. These habits may result in physical complaints such as neck, back, and shoulder pain. This study aimed to examine the association between sitting duration and learning posture with musculoskeletal complaints among high school students. A quantitative approach with a cross-sectional design was employed. The sample consisted of 120 students selected using proportionate stratified random sampling. Data were collected using the Nordic Musculoskeletal Questionnaire (NMQ) and posture observation sheets. Data analysis was conducted using the Kruskal–Wallis test with a significance level of 0.05. The findings revealed that the majority of students who spent more than 6 hours per day sitting with a slouched posture reported moderate to severe musculoskeletal complaints, particularly in the neck (68%), upper back (61%), and shoulders (54%). Statistical analysis showed a significant association between sitting duration and learning posture with the severity of musculoskeletal complaints (p = 0.041). In conclusion, there is a significant association between sitting duration and learning posture with musculoskeletal complaints among high school students. Ergonomic education and light physical interventions should be implemented in schools to prevent musculoskeletal disorders from an early age.